TAX POLICY IN THE DIGITAL ECONOMY IN THE REPUBLIC OF UZBEKISTAN AND ITS IMPACT ON THE MECHANISM OF INDIRECT TAXES - Djalilov Rakhmonkul Hamidovich (European Science Publishing, 2025)
This article examines the impact of tax policies implemented in the tax sector in the context of the digital economy on the mechanisms for accounting for indirect taxes in the tax system.
Keywords: Digital economy, tax system, tax control, tax administration, indirect taxes, electronic and digital taxation